Model of Community and Family Development to Care for The Elderly Master Integrated on the Outbreak of The Coronavirus Disease 2019 - Soiphet, Nutcha; Kunalasiri, Petcharee (Journal of The Royal Thai Army Nurses, 2024)
This participatory action research aimed to 1) develop the model of community and family development to care for the elderly master integrated on the outbreak of the coronavirus disease 2019 and 2) study the effectiveness of the model. The research operation was divided into two steps. Step 1 involved developing a model for community and family development. The sample group consists of community leaders, village volunteers, elderly caregivers, and public health officials, totaling 30 people join the community forum to exchange knowledge and brainstorm ideas for designing. Data analysis techniques was content analysis. These findings resulted in a framework of educational activities consisting of 7 topics: 1) providing information and news 2) listening to opinions 3) collaboration and building partnerships 4) leadership 5) managing care plans for the elderly related to COVID-19 6) promoting health and preventing COVID-19 among the elderly 7) caring for physical, mental, and spiritual well-being 8) ensuring the safety and well-being of the community. Step 2: studied the effectiveness of the model. The model was implemented with 210 primary caregivers in the Pai Kho Don sub-district. Test the model by organizing educational activities on 7 topics for 2 hours each week, totaling 6 consecutive weeks, with assessments conducted twice: once before the trial and once after the trial ends, 4 weeks later. Descriptive statistics and t-tests was used. The results showed that the sample group showed a statistically significant increase in the average scores for community and family role activities, as well as integrated elderly care, compared to before the intervention (P<.05).